2010
DOI: 10.2353/ajpath.2010.090299
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Interleukin-6 and Parathyroid Hormone-Related Peptide in Osteoclast Formation Associated with Oral Cancers

Abstract: We investigated the roles of interleukin-6 (IL-6) and parathyroid hormone-related peptide (PTHrP) in oral squamous cell carcinoma (OSCC)-induced osteoclast formation. Microarray analyses performed on 43 human OSCC specimens revealed that many of the specimens overexpressed PTHrP mRNA, but a few overexpressed IL-6 mRNA. Immunohistochemical analysis revealed that IL-6 was expressed not only in cancer cells but also in fibroblasts and osteoclasts at the tumor-bone interface. Bone invasion by various malignant tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 45 publications
3
69
0
Order By: Relevance
“…Several oral SCC cells in patients and oral SCC cell lines express RANKL (38)(39)(40). Recently, Chuang et al compared RANKL expression between buccal SCC without bone invasion (25 cases) and gingival SCC with invasion (15 cases).…”
Section: Rankl/rank Signaling Is Involved In Oral Scc Cell-induced Osmentioning
confidence: 99%
“…Several oral SCC cells in patients and oral SCC cell lines express RANKL (38)(39)(40). Recently, Chuang et al compared RANKL expression between buccal SCC without bone invasion (25 cases) and gingival SCC with invasion (15 cases).…”
Section: Rankl/rank Signaling Is Involved In Oral Scc Cell-induced Osmentioning
confidence: 99%
“…The bidirectional tumor-stromal interaction often takes place at the TB interface where tumor cell-derived cytokines stimulate osteoclast differentiation, resulting in degradation of the bone matrix and the release of bone-derived cytokines that further promote tumor growth [1,26]. The activated factors at the TB interface implied the involvement of them in the tumor-stromal interaction [27,29,30]. We utilized a model of bone metastasis which was confirmed as a fine model to replicate the tumor-induced changes in bone microenvironment [31].…”
Section: Discussionmentioning
confidence: 99%
“…Many of studies showed that IHC plays an important role in pathology and particularly in the subspecialties of oncologic pathology , neuropathology and hematopathology , The first IHC study was reported at 1941 but the principle of immunohistochemistry has existed since the 1930s (Ajura et al .,2007). Kayamori et al (2010) were examined the expression of IL-6 to revealed that was this expression not only in cancer cells but also in fibroblasts and osteoclasts at the tumor bone interface. While, Becker et al (2005) were demonstrated that IL-6 can regulate the proliferation of intestinal epithelial cells (IEC) and inducing growth of dysplastic lesion in vivo as possible functional role of interleukin-6.…”
Section: Introductionmentioning
confidence: 99%